The Principle of Good Faith in Settlement of Default Disputes Through Judicial Mediation - Wika Yudha Shanty (Jurnal Cakrawala Hukum, 2023)
Mediation based on good faith is one of the characteristics of the Indonesian nation to resolve disputes that occur, starting from the smallest scope, namely the family, to the large scope, such as in government and statehood. With the birth of the Supreme Court Regulation of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures in Court. Focus on this article on the nature and implications of the principle of good faith in resolving default disputes due to the non-implementation of agreements through judicial mediation. So it is hoped that the mediation process can overcome the problem of case accumulation. If a dispute can be resolved through mediation, there is no need for further legal remedies such as appeals, cassation, and even judicial review, which leads to the Supreme Court, so there is a buildup of cases. In addition, the mediation process, which is a non-litigation process, is a faster settlement process and has low costs compared to the litigation process through trial.How to cite item: Shanty, Wika Yudha. â€œThe Principle of Good Faith in Settlement of Default Disputes Through Judicial Mediation.â€ Jurnal Cakrawala Hukum 14 no. 2 (2023): 223-233. DOI: 10.26905/idjch.v14i2.10863.Â